2020
DOI: 10.1186/s12864-020-6503-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the Gossypium hirsutum L. respiratory burst oxidase homolog (Ghrboh) gene family

Abstract: Background: Plant NADPH oxidase (NOX), also known as respiratory burst oxidase homolog (rboh), encoded by the rboh gene, is a key enzyme in the reactive oxygen species (ROS) metabolic network. It catalyzes the formation of the superoxide anion (O 2 •−), a type of ROS. In recent years, various studies had shown that members of the plant rboh gene family were involved in plant growth and developmental processes as well as in biotic and abiotic stress responses, but little is known about its functional role in up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 90 publications
7
19
0
Order By: Relevance
“…Both G. arboretum and G. raimondii harbored 13 Rboh genes, a result that agrees with the findings of Zhang et al (2020). The main difference with that work is that we found 24 and 27 Rboh genes in G. hirsutum and G. barbadense, while they found 26 and 19, respectively (Wang et al, 2020). For G. hirsutum, 4 of 26 GhRbohs were anchored to unmapped scaffolds in the NAU-NBI v1.1 assembly genome (assembled in 2015), whereas we found that all 24 GhRbohs in the HAU v1.0 assembly genome (assembled in 2018) mapped onto the A t or D t sub-genome chromosomes.…”
Section: Discussionsupporting
confidence: 87%
“…Both G. arboretum and G. raimondii harbored 13 Rboh genes, a result that agrees with the findings of Zhang et al (2020). The main difference with that work is that we found 24 and 27 Rboh genes in G. hirsutum and G. barbadense, while they found 26 and 19, respectively (Wang et al, 2020). For G. hirsutum, 4 of 26 GhRbohs were anchored to unmapped scaffolds in the NAU-NBI v1.1 assembly genome (assembled in 2015), whereas we found that all 24 GhRbohs in the HAU v1.0 assembly genome (assembled in 2018) mapped onto the A t or D t sub-genome chromosomes.…”
Section: Discussionsupporting
confidence: 87%
“…The amount of AGPases increased by whole-genome duplication in sweetpotatoes from its relatives. This result is consistent with a study showing that the number of rboh genes in the polyploid plant, Gossypium hirsutum, was higher than its progenitor plants G. raimonddi and G. arboreum (Wang et al 2020). Moreover, some AGPases in I. tri da and I. triloba exhibited an II value ≥ 40, which means an unstable state, but there was no AGPase representing an II value ≥ 40 in I. batatas (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…Chlamydomonas reinhardtii (chlorophyte alga), but not from the other three chlorophyte algae tested (Micromonas pusilla, Ostreococcus lucimarinus and Volvox carteri) (Wang et al, 2020). Previous studies also identified RBOH homologues in some red alga species, such as Cyanidioschyzon merolae .…”
Section: Evolution Of Rboh Protein Familymentioning
confidence: 95%